Detailaufnahme vom Ulli Beier-Schrein, zwei kupferne kleine Skulpturen (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2014)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Africa; Art; Artists; Interior decoration; Orisha religion; Yoruba (African people)–Religion; Sculpture; Photographs; Shrine; Yoruba Art; Art Collector; Art Collecting; Wood Sculpture